Blockage of 5HT(2C) serotonin receptors by fluoxetine (Prozac) - Ni, Y. G. (The National Academy of Sciences of the USA, 1997)
Fluoxetine (Prozac) inhibited the membrane currents elicited by serotonin (5-hydroxytryptamine; 5HT) in Xenopus oocytes expressing either cloned 5HT(2C) receptors or 5HT receptors encoded by rat cortex mRNA. Responses of 5HT(2C) receptors, elicited by nM concentrations of 5HT, were rapidly and reversibly blocked by micromolar concentrations of fluoxetine. For responses elicited by 1 μM 5HT, the IC(50) of fluoxetine inhibition was ≈20 μM. In accord with the electrophysiological results, fluoxetine inhibited the binding of [(3)H]5HT to 5HT(2C) receptors expressed in HeLa cells (K(i) ≈ 65–97 nM), and the binding to 5HT receptors in rat cortex membranes was also inhibited but less efficiently (K(i) ≈ 56 μM). Our results show that fluoxetine is a competitive and reversible antagonist of 5HT(2C) receptors and suggest that some therapeutic effects of fluoxetine may involve blockage of 5HT receptors, in addition to its known blockage of 5HT transporters. Similar work may help to design more selective compounds for use in the treatment of brain disorders.